Factores relacionados con la nutrición y la adherencia al tratamiento farmacológico en pacientes con hipertensión arterial no controlada en el Centro de Salud Pimocha, cantón Babahoyo, junio - octubre del 2023. - Correa Villacis, Jomira Jamilet (2023)
In summary, this research aims to shed light on the factors influencing the adherence to pharmacological and nutritional treatment in patients with uncontrolled arterial hypertension at the Pimocha Health Center in the Babahoyo Canton. To achieve this, a detailed analysis of the patients´ demographic and economic characteristics is conducted, along with the identification of factors conditioning or facilitating treatment adherence. These findings are highly relevant as they determine the success of therapy in this population. The results are not only of academic importance but also have a significant impact on the medical care provided to patients in this rural community. The survey conducted reveals a concerning lac of treatment adherence, highlighting the necessity of this study for both patients and the healthcare personnel who attend to them. It is crucial to emphasize that this research addresses a relevant public health public health issue in the region, as arterial hypertension is a chronic condition affecting a significant proportion of the adult population, and its control is essential to prevent serious complications such as cardiovascular diseases.